Development of Interactive Teaching Modules as an Effort to Improve Students' Understanding of Plane Shapes - Rindy Aiwan; Aan Nurhasanah; Eli Hermawati (JINoP (Jurnal Inovasi Pembelajaran), 2026)
Background: The problem with this research is that the teaching materials used are only worksheets. At the elementary and secondary school level, only 15% of teachers develop their own teaching modules. Objectives: The objectives of this research were to determine how to develop an interactive teaching module for phase B of geometry elements on plane shapes, to determine the feasibility of the interactive teaching module, and to determine the effectiveness of students using the interactive teaching module for phase B of geometry elements on plane shapes. Methods: This research method is Research and Development, a modification of Borg & Gall's method, which divides it into three stages: preliminary study, development, testing, and dissemination. Data collection techniques in this study included interviews, expert product assessment, effectiveness testing, and student response questionnaires. Data analysis techniques used were interactive qualitative data and quantitative data (validity testing, effectiveness testing, and student response questionnaire analysis). Results: The validation results obtained an average of 0.89, which can be interpreted as a high coefficient. Based on the student response questionnaire, 98.6% obtained, meaning it is "very suitable" for use. Based on the main trial, the average student score before using the interactive learning module was 54.54, while after using the interactive learning module, it was 73.86. The results of the Paired Sample T-test showed a calculated t value > t table, with a value of 3.272 > 2.080, indicating a significant difference in student learning outcomes after using the interactive learning module. Conclusions: This research resulted in a valid, feasible, and effective interactive learning module phase B for geometry elements in plane shapes. Its implementation significantly improved learning outcomes and received a very positive student response.